Pengaruh Rebusan Jahe Merah Terhadap Dismenore Pada Remaja Putri di SMK Assalaam Manado - Rosaliya Katili; Agust A. Laya; Kristine Dareda (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
Dysmenorrhea is a pain in the lower abdomen can spread to the lower back and legs. The incidence of dysmenorrhea in the world on average is very high up to (90%) while the severe painful dysmenorrhea are around 10-15%. In Indonesia the case of dysmenorrhea is around of 64.25%. The aim of this research was to determine the effectiveness of giving red ginger decoction on dysmenorrhea in young women at Assalaam Vocational School, Manado. This research uses a pre-experimental quantitative method with one group pre and post test design. wWith non-probability sampling technique and purposive sampling method based on characteristics of the population by the criteria of the researcher's. The research instrument uses an observation sheet and a Standard Operating Procedure for measurement using the NRS (Numeric Rating Scale). The sample in this study takes 12 respondents. Using the Pairet T-Test with a significance level of α=0.05. The results of this study show there is an effect of giving red ginger decoction on dysmenorrhea in young women with a P-value = 0.000 < 0.05 The conclusion in this study is giving red ginger decoction on dysmenorrhea in young women at Assalaam Vocational School, Manado are affected. And advice to respondents to used red ginger as an additional reference for reducing pain during dysmenorrhea.